Advances in cellular and molecular predatory biology of Bdellovibrio bacteriovorus six decades after discovery - Lai, Ting F.; Ford, Rhian M.; Huwiler, Simona G. (Frontiers in Microbiology, 2023)
Since its discovery six decades ago, the predatory bacterium Bdellovibrio bacteriovorus has sparked recent interest as a potential remedy to the antibiotic resistance crisis. Here we give a comprehensive historical overview from discovery to progressive developments in microscopy and molecular mechanisms. Research on B. bacteriovorus has moved from curiosity to a new model organism, revealing over time more details on its physiology and fascinating predatory life cycle with the help of a variety of methods. Based on recent findings in cryo-electron tomography, we recapitulate on the intricate molecular details known in the predatory life cycle including how this predator searches for its prey bacterium, to how it attaches, grows, and divides all from within the prey cell. Finally, the newly developed B. bacteriovorus progeny leave the prey cell remnants in the exit phase. While we end with some unanswered questions remaining in the field, new imaging technologies and quantitative, systematic advances will likely help to unravel them in the next decades.